HUBUNGAN POLA ASUH ORANG TUA DENGAN TINGKAT KEMANDIRIAN ANAK RETARDASI MENTAL RINGAN DI SDLB YPLB BANJARMASIN - Vonny Khresna Dewi (An-Nadaa: Jurnal Kesehatan Masyarakat (e-Journal), 2017)
Mental retardation populations keep the greatest numbers compared to other children. WHO data in 2012 prevelensi mental retardation in Indonesia is currently estimated at 1-3% of the population of Indonesia about 6.6 million people. Independence in children starts from the family also by parenting parents. In the family, parents are instrumental in nurturing, guiding and helping to direct the child to become independent. This research is intended to find out the relationship between parenting parenting with the level of independence of children with mild mental retardation in SDLB YPLB Banjarmasin in 2016. This study used analytical method with cross sectional approach. The population is all parents who have children of mild mental retardation in SDLB YPLB Banjarmasin need 40 people with sample 35 people. Sampling technique by purposive sampling. Data collection with questionnaire and data analysis with univariate analysis and bivariate analysis (Spearman Rank test). The result of this research was obtained from 35 respondents mostly 25 people (71,4%) parents using authoritarian parenting and mental retardation children's independence is 20 people (57,1%). There is a relationship between parenting parenting with the level of independence of children with mild mental retardation in SDLB YPLB Banjarmasin Year 2016. It is suggested at school to further improve the provision of health information to parents about democratic parenting and trained also at home in order to improve independence